High-temperature ablation resistant ceramic-based composite material and preparation method thereof
Through the cross-linking and chemical vapor-permeation technology of rare earth acetylacetone complex and carbide precursor, carbon fiber-reinforced carbide ceramic-rare earth zirconate or carbide ceramic-rare earth hafnate ceramic-rare earth hafnate ceramic-based composite materials were prepared, and MoSi2 was introduced on the surface, solving the problem of insufficient ablation and high-temperature mechanical properties of ceramic matrix composites in the prior art under high-temperature ablation conditions, and achieving better resistance to high-temperature ablation and mechanical properties.
Patent Information
- Application Number
- CN202411728758.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, carbon fiber reinforced ceramic matrix composite materials have poor ablation resistance under high-temperature ablation conditions and have poor high-temperature mechanical properties, making it difficult to meet the needs of high-tech fields.
By crosslinking rare earth acetylacetone complex with polyzirconium oxide or polyhafnoxane to form a ceramic precursor, combined with the precursor impregnation and cracking process and chemical vapor-phase permeation method, a carbon fiber-reinforced carbide ceramic-rare earth zirconate or carbide ceramic-rare earth hafnoxane ceramic-rare earth hafnoxane ceramic-based composite material was prepared, and MoSi2 was introduced on the surface to form a hierarchical structure rich in molybdenum disilide.
It significantly improves the high-temperature ablation and high-temperature mechanical properties of ceramic matrix composites, reduces the damage to carbon fibers by high-temperature cracking temperature, and enhances the overall performance of the material.
Smart Images

Figure BDA0005159798370000261
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to a high-temperature ablation-resistant ceramic-based composite material and a preparation method thereof. Background Art
[0002] Carbon fiber reinforced ceramic matrix composites are a new type of composite material that uses continuous carbon fiber as a toughening phase and high-performance ceramics as a matrix. They have both the high strength of ceramics and the toughness of continuous carbon fiber. f / ZrC) and carbon fiber reinforced hafnium carbide (C f / HfC) exhibits excellent high-temperature performance in harsh environments such as high temperature and strong airflow, and is widely used in high-tech fields such as aerospace.
[0003] At present, the precursor impregnation pyrolysis technology (PIP) is a process that impregnates liquid ceramic precursors into carbon fiber preforms, and forms a ceramic matrix after curing and high-temperature pyrolysis. It is widely used in the preparation of carbon fiber due to its advantages such as simple equipment requirements and near-net-shape molding. f / ZrC and C f For example, Chinese patent application CN105367106A discloses a method for preparing C / HfC composite materials by periodically impregnating, curing and cracking a zirconium source and a carbon source to densify a carbon fiber matrix. f / ZrC composite material method, the method promotes the carbothermal reduction reaction by increasing the pyrolysis temperature, increases the ZrC yield and thus improves the anti-ablation performance of the composite material, but the high pyrolysis temperature and carbothermal reduction reaction used in this method cause great damage to the fiber, resulting in poor mechanical properties of the obtained ceramic-based composite material.
[0004] As the high temperature ablation conditions become more stringent, the C f / ZrC and C f During the ablation process of / HfC composite materials, porous ZrO2 and HfO2 are oxidized. The ablation layer has poor adhesion and is easy to peel off, and it is easy to lose the protective ability of the substrate prematurely. Chinese patent application CN117602943A discloses a method for preparing a ceramic-based composite material using an oxygen-free tantalum titanium precursor, and uses high temperature and high pressure conditions to increase the sintering degree of titanium carbide and tantalum carbide. Titanium carbide and tantalum carbide can form titanium oxide and tantalum oxide anti-ablation components under high temperature ablation conditions, but the formed oxides are also loose and porous, and the anti-ablation layer has poor anti-stripping behavior. Although this method improves the sintering degree of titanium carbide and tantalum carbide and improves its high-temperature ablation resistance to a certain extent, the method of increasing the sintering degree is relatively harsh (1600℃, 9MPa), and has high requirements for the preparation equipment. At the same time, the higher sintering temperature will also cause the mechanical properties of the fiber to be damaged, further reducing the comprehensive performance of the ceramic-based composite material.
[0005] Therefore, it is urgent to develop a ceramic-based composite material that is resistant to high-temperature ablation and a preparation method thereof, so as to improve its ablation resistance while reducing the oxidation of carbon fiber during the precursor pyrolysis process and avoiding damage to the mechanical properties of carbon fiber caused by excessively high pyrolysis temperature. Summary of the invention
[0006] In order to solve one or more technical problems existing in the prior art, the present invention provides a ceramic-based composite material resistant to high-temperature ablation and a preparation method thereof.
[0007] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material resistant to high temperature ablation, the method comprising the following steps:
[0008] (1) preparing a porous carbon fiber preform;
[0009] (2) preparing a rare earth acetylacetone complex using a hexahydrate of a rare earth chloride or a hexahydrate of a rare earth nitrate and acetylacetone;
[0010] (3) mixing the rare earth acetylacetone complex and polyzirconium oxide or polyhafnium oxide uniformly with xylene to obtain a zirconium-rare earth ceramic precursor solution or a hafnium-rare earth ceramic precursor solution;
[0011] (4) using a zirconium-rare earth ceramic precursor solution or a hafnium-rare earth ceramic precursor solution as an impregnation liquid, and performing a first densification on the porous carbon fiber preform through a precursor impregnation and cracking process to obtain a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material;
[0012] (5) Using molybdenum chloride and silicon chloride as raw materials, a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material is subjected to a second densification by a chemical vapor infiltration method to obtain a ceramic matrix composite material resistant to high temperature ablation.
[0013] Preferably, in step (1), the porous carbon fiber preform is obtained by depositing an interface layer on the fibers of the carbon fiber braid; preferably, the density of the carbon fiber braid is 0.4 to 0.6 / cm 3 ; Preferably, the interface layer is one or more of a pyrolytic carbon interface layer, a silicon carbide interface layer or a boron nitride interface layer; Preferably, the density of the porous carbon fiber preform is 0.7 to 1.2 g / cm 3 .
[0014] Preferably, in step (2), the rare earth acetylacetone complex is prepared by uniformly mixing rare earth chloride hexahydrate or rare earth nitrate hexahydrate with acetylacetone using an ethanol solution to obtain a mixed solution, then adjusting the pH of the mixed solution to 5.5-6.5 using aqueous ammonia and keeping the mixture at 50-70°C for 1-2 hours, and then filtering, washing, crystallizing and drying to obtain the rare earth acetylacetone complex.
[0015] Preferably, the hexahydrate of the rare earth chloride is RECl3·6H2O, wherein RE is selected from one or more of La, Sm, Gd, Tb, Dy or Yb; the hexahydrate of the rare earth nitrate is RE(NO3)3·6H2O, wherein RE is selected from one or more of La, Sm, Gd, Tb, Dy or Yb; the molar ratio of the hexahydrate of the rare earth chloride to acetylacetone is 1:(3-4), and the molar ratio of the hexahydrate of the rare earth nitrate to acetylacetone is 1:(3-4); the ethanol solution is an ethanol aqueous solution, and the volume percentage of ethanol in the ethanol aqueous solution is 90-98%; and / or the ammonia water is ammonia water with a mass fraction of 20-30%.
[0016] Preferably, in step (3), the molar ratio of the rare earth acetylacetone complex to polyzirconia is 1:(1.5-3), and the zirconium-rare earth ceramic precursor solution contains a sum of the mass fractions of the rare earth acetylacetone complex and polyzirconia in an amount of 40%-60%.
[0017] Preferably, in step (3), the molar ratio of the rare earth acetylacetone complex to polyhafnium oxide is 1:(1.5-3), and the hafnium-rare earth ceramic precursor solution contains a sum of the mass fractions of the rare earth acetylacetone complex and polyhafnium oxide of 40%-60%.
[0018] Preferably, in the precursor impregnation pyrolysis process in step (4): the pyrolysis temperature is 1300-1500°C, the pyrolysis time is 1.5-3h; and / or the obtained carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material has a density of 2.2-2.5g / cm 3 .
[0019] Preferably, in step (5): the molybdenum chloride is molybdenum tetrachloride; the silicon chloride is silicon tetrachloride; when chemical vapor infiltration is performed, hydrogen and argon are used as carrier gases; the pressure during chemical vapor infiltration is 50-200 mbar, and the temperature is 900-1200°C; and / or when chemical vapor infiltration is performed, the flow rate of the molybdenum chloride is 10-50 sccm, the flow rate of the silicon chloride is 50-200 sccm, the flow rate of the hydrogen is 80-300 sccm, and the flow rate of the argon is 100-400 sccm.
[0020] Preferably, in step (5): chemical vapor infiltration is performed until the density of the obtained high temperature ablation resistant ceramic matrix composite material is 2.7 to 3.0 g / cm 3 The obtained high temperature ablation resistant ceramic matrix composite material is a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material with a surface rich in molybdenum disilicide or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material with a surface rich in molybdenum disilicide.
[0021] In a second aspect, the present invention provides a high temperature ablation resistant ceramic matrix composite material prepared by the preparation method described in the first aspect of the present invention.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] (1) Chinese patent application CN105367106A and Chinese patent application CN117602943A use zirconium carbide and other ultra-high temperature ceramics as anti-ablation components. Under high-temperature ablation conditions, an anti-ablation layer of oxides such as zirconium oxide is formed on the surface of the carbide ceramics to improve the anti-ablation performance of the ceramic-based composite material. However, the formed zirconium oxide and other oxides are loose and porous, and the anti-ablation layer has low bonding strength with the matrix and is easy to peel off, and cannot form a continuous protection for the ceramic-based composite material. The present invention has found that rare earth zirconates and rare earth hafnates have high melting points and excellent high-temperature phase stability, excellent resistance to high-temperature oxidation and ablation, and can achieve excellent anti-ablation effects without forming an anti-ablation layer at high temperatures, and have better continuous protection effects on ceramic substrates. The present invention forms a carbon fiber reinforced carbide ceramic-rare earth zirconate (rare earth hafniumate) ceramic-based composite material by cross-linking a rare earth acetylacetone complex with polyzirconium oxane (or polyhafnium oxane), and solidifying and cracking the precursor in a carbon fiber preform. The present invention introduces rare earth elements into the ceramic-based composite material, and reacts with the zirconium-based (or hafnium-based) precursor at high temperature to generate rare earth zirconates (or rare earth silicates) and zirconium carbide (or hafnium carbide), thereby improving the anti-ablation performance of the ceramic-based composite material.
[0024] (2) Polyzirconia (or polyhafnium oxide) is cracked at a relatively low temperature, and the carbon thermal reduction reaction is not completely completed. The products are zirconium oxide (or hafnium oxide) and zirconium carbide (hafnium carbide). The difference in thermal expansion coefficient between zirconium oxide (or hafnium oxide) and carbon fiber is large, and a large thermal mismatch stress may be generated inside the composite material, causing the material to crack or performance degradation. In addition, zirconium oxide (or hafnium oxide) will undergo a phase change during the cooling process from high temperature to room temperature, causing the volume to expand, resulting in stress concentration inside the composite material, affecting the overall performance and stability of the material. Chinese patent application CN105367106A completes the carbon thermal reduction reaction by increasing the cracking temperature, thereby generating a zirconium carbide matrix and reducing the content of zirconium oxide in the matrix. However, excessively high cracking temperatures and carbon thermal reduction reactions will cause damage to the carbon fiber, resulting in a decrease in its mechanical properties, affecting the final service effect of the ceramic-based composite material. The present invention uses a relatively low cracking temperature and does not require polyzirconium oxide (or polyhafnium oxide) to completely complete the carbon thermal reduction reaction. The zirconium oxide (or hafnium oxide) formed by cracking is used as a zirconium source (or hafnium source), a rare earth acetylacetone complex is used as a rare earth source, and an oxygen-containing functional group in a precursor is used as an oxygen source to react and form a rare earth zirconate (or rare earth hafnium oxide) with better anti-ablation performance. While reducing the content of zirconium oxide or hafnium oxide in the matrix, the damage to the carbon fiber caused by high temperature and carbon thermal reduction reaction is reduced, which is beneficial to improving the mechanical properties of the ceramic-based composite material.
[0025] (3) The present invention uses acetylacetone complex of rare earth as rare earth source, which can be evenly mixed with polyzirconia (or polyhafnium) in xylene compared with rare earth oxide ceramic particles, which is more conducive to the impregnation of rare earth source and the uniform dispersion distribution of rare earth zirconate (or rare earth hafnium) in ceramic matrix composite material; in addition, the present invention combines the characteristics of MoSi2 with high temperature oxidation resistance and the ability to promote the sintering of ZrC and HfC, and introduces MoSi2 into ceramic matrix composite material by CVI method, which improves the oxidation resistance of ceramic matrix composite material on the one hand, and improves the sintering of ZrC and HfC in high temperature service environment on the other hand, which helps to form a dense anti-ablation oxide film, and further improves the anti-ablation performance of ceramic matrix composite material. Compared with CN117602943A, the present invention can improve the anti-ablation performance of ceramic matrix composite material without using high temperature and high pressure methods that are demanding on equipment and relatively costly. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material resistant to high temperature ablation, the method comprising the following steps:
[0028] (1) preparing a porous carbon fiber preform;
[0029] (2) preparing a rare earth acetylacetone complex using a hexahydrate of a rare earth chloride or a hexahydrate of a rare earth nitrate and acetylacetone;
[0030] (3) mixing the rare earth acetylacetone complex and polyzirconium oxide or polyhafnium oxide uniformly with xylene to obtain a zirconium-rare earth ceramic precursor solution or a hafnium-rare earth ceramic precursor solution; in this step (3), the rare earth acetylacetone complex and polyzirconium oxide or polyhafnium oxide are cross-linked to form a ceramic precursor. Specifically, the rare earth acetylacetone complex and polyzirconium oxide are uniformly stirred in xylene to obtain a zirconium-rare earth ceramic precursor solution, and the rare earth acetylacetone complex and polyhafnium oxide are uniformly stirred in xylene to obtain a hafnium-rare earth ceramic precursor. Solution; The present invention does not specifically limit the source of polyzirconia oxide and polyhafnoxane, and can use products that can be directly purchased or synthesized by existing methods; In step (3) of the present invention, the stirring temperature can be, for example, 20 to 50° C. to avoid side reactions caused by high temperature, and the stirring speed can be, for example, 500 to 1000 rpm to ensure uniform mixing. The stirring time depends on the viscosity and uniformity requirements of the mixture, and usually needs to be stirred for 30 to 120 minutes until the mixture is uniform and there is no obvious stratification;
[0031] (4) using a zirconium-rare earth ceramic precursor solution or a hafnium-rare earth ceramic precursor solution as an impregnation liquid, and performing a first densification on a porous carbon fiber preform through a precursor impregnation pyrolysis process (PIP process) to obtain a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material; the PIP process in step (4) is to use a zirconium (hafnium)-rare earth ceramic precursor as a reactant, and perform a densification on a porous carbon fiber preform through a precursor impregnation pyrolysis process (PIP process) to obtain a carbon fiber reinforced carbide ceramic-rare earth zirconate (or rare earth hafniumate) ceramic matrix composite material;
[0032] (5) Using molybdenum chloride (MoCl4) and silicon chloride (SiCl4) as raw materials, a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material is subjected to a second densification by a chemical vapor infiltration method (CVI method) to obtain a high-temperature ablation-resistant ceramic matrix composite material; in step (5), a carbon fiber reinforced carbide ceramic-rare earth zirconate (or rare earth hafniumate) ceramic matrix composite material with a surface rich in molybdenum disilicide (MoSi2) is formed, that is, the high-temperature ablation-resistant ceramic matrix composite material is obtained; the present invention finds that the introduced molybdenum disilicide, in addition to having excellent anti-oxidation and ablation properties, can also be used as a sintering aid to promote the sintering of ZrC and HfC in a high-temperature service environment, which helps to form a dense ablation-resistant oxide film, thereby further improving the ablation-resistant performance of the ceramic matrix composite material.
[0033] The present invention solves the problem of preparing C by the PIP method in the prior art. f / ZrC and C f The problem of poor high-temperature oxidation and ablation resistance and high-temperature mechanical properties of HfC composite materials above 2000°C is solved. The present invention cross-links a rare earth acetylacetone complex with polyzirconium oxane (or polyhafnium oxane) to form a precursor, and pyrolyzes it at a relatively low temperature to form a rare earth zirconate or a rare earth hafnium salt. This not only reduces the oxidation damage of the oxygen in the precursor to the carbon fiber, but also avoids the damage to the carbon fiber at an excessively high pyrolysis temperature, thereby maintaining the mechanical properties of the fiber. At the same time, the generated rare earth zirconate or hafnium salt has excellent phase stability and high-temperature oxidation and ablation resistance at high temperatures, thereby effectively improving the ablation resistance of the ceramic-based composite material. Although Chinese patent application CN201410116784.4 discloses A method for preparing a carbon fiber reinforced ultra-high temperature ceramic matrix composite material that can be repeatedly ablated, but the patent application forms rare earth zirconate or rare earth hafnium salt by the method of reaction infiltration of high temperature alloy, the process temperature is high, the fiber damage is large, and the residual metal in the reaction infiltration will cause stress concentration in the composite material, further weakening the mechanical properties of the composite material; in addition, the present invention uses rare earth acetylacetone complex as a rare earth source, which can be uniformly mixed with polyzirconium oxide (or polyhafnium oxide) in xylene, which is conducive to the impregnation of rare earth source and the uniform dispersion distribution of rare earth zirconate (or rare earth hafnium salt) in the ceramic matrix composite material, and this uniform distribution helps to improve the overall performance of the ceramic matrix composite material, including anti-ablation performance and mechanical properties. Compared with the slurry formed by rare earth oxide particles combined with a dispersant for impregnation in Chinese patent application CN201410116784.4, the distribution uniformity of rare earth elements in the present invention is better, and the overall performance of the formed ceramic matrix composite material is also better.
[0034] The present invention introduces MoSi2 by chemical vapor infiltration (CVI) to form a carbon fiber reinforced carbide ceramic-rare earth zirconate (or rare earth hafniumate) ceramic matrix composite material with a surface rich in MoSi2. MoSi2 itself has excellent anti-oxidation and ablation properties, and as a sintering aid, it can promote the sintering of zirconium carbide (or hafnium carbide) at high temperatures, further improving the ablation resistance of the ceramic matrix composite material. Although the ceramic matrix composite material in Chinese patent application CN201510540837.X also introduces MoSi2, the patent application introduces MoSi2 by vacuum filtration-homogeneous hydrothermal deposition. Compared with the vacuum filtration-homogeneous hydrothermal deposition method in patent application CN201510540837.X, the present invention can more effectively form a MoSi2-enriched layer with high ablation resistance on the surface of the composite material, thereby providing better protection under harsh high-temperature ablation conditions. In addition, the heat treatment step in patent application CN201510540837.X needs to be carried out at 1400-1600°C. This high-temperature treatment may damage the carbon fiber and affect the overall performance of the composite material. The chemical vapor infiltration (CVI) method used in the method of the present invention introduces MoSi2 with a low deposition temperature (900-1200°C), which has a relatively low effect on the mechanical properties of the ceramic-based composite material.
[0035] According to some preferred embodiments, in step (1): the porous carbon fiber preform is obtained by depositing an interface layer on the fibers of a carbon fiber braid; the porous carbon fiber preform uses a carbon fiber braid as a skeleton, and the braiding method can be any one of acupuncture, suturing or puncture. The present invention does not specifically limit the source of the carbon fiber braid, and can be a product that can be directly purchased or prepared by an existing method; preferably, the density of the carbon fiber braid is 0.4 to 0.6 / cm 3 (e.g. 0.4, 0.45, 0.5, 0.55 or 0.6 g / cm 3 ); the fibers of the carbon fiber braid have an interface layer deposited by chemical vapor deposition (CVD) or the like, and the types of the interface layer include but are not limited to one or more of pyrolytic carbon (PyC), silicon carbide (SiC) or boron nitride (BN); preferably, the interface layer is one or more of a pyrolytic carbon interface layer, a silicon carbide interface layer or a boron nitride interface layer; preferably, the density of the porous carbon fiber preform is 0.7 to 1.2 g / cm 3 (e.g. 0.7, 0.8, 0.9, 1.0, 1.1 or 1.2 g / cm 3 ); The present invention does not specifically limit the CVD process conditions for depositing the interface layer, which is a conventional technique in the art. Preferably, the density of the porous carbon fiber preform after depositing the interface layer is 0.7 to 1.2 g / cm 3 That's it.
[0036] According to some preferred embodiments, in step (2), the rare earth acetylacetone complex is prepared by: mixing rare earth chloride hexahydrate or rare earth nitrate hexahydrate with acetylacetone with ethanol solution to obtain a mixed solution, then adjusting the pH of the mixed solution to 5.5-6.5 (e.g., 5.5, 5.7, 5.9, 6.1, 6.3 or 6.5) with aqueous ammonia and keeping the mixed solution at 50-70°C (e.g., 50°C, 55°C, 60°C, 65°C or 70°C) for 1-2 hours (e.g., 1, 1.2, 1.4, 1.6, 1.8 or 2 hours), then filtering, washing, crystallizing and drying to obtain the rare earth acetylacetone complex; in the present invention, in the mixed solution, the amount of the ethanol solution is, for example, 4-15 times (e.g., 4, 6, 8, 10, 12, 14 or 15 times) the sum of the mass amounts of the rare earth chloride hexahydrate and acetylacetone, or the ethanol solution is 100% by weight. The amount of the alcohol solution is, for example, 4 to 15 times (for example, 4, 6, 8, 10, 12, 14 or 15 times) the sum of the mass amounts of the hexahydrate of rare earth nitrate and acetylacetone; the present invention does not specifically limit the filtering method, which is a conventional technique in the art; in the present invention, a crude product of a rare earth acetylacetone complex is obtained after filtration, and then a small amount of ethanol solution is used to wash and crystallize the crude product of the rare earth acetylacetone complex to remove the attached mother liquor and solvent, and the rare earth acetylacetone complex is obtained after drying; preferably, the volume percentage (volume fraction) of ethanol contained in the ethanol solution used for washing the crystallization is 90 to 98% (for example, 90%, 92%, 94%, 96% or 98%), and the drying temperature of the crystals after washing and crystallization is 60 to 80°C (for example, 60°C, 65°C, 70°C, 75°C or 80°C), and the present invention does not specifically limit the drying time, and drying to constant weight is sufficient.
[0037] In the preparation of the rare earth acetylacetone complex in step (2) of the present invention, it is necessary to adjust the pH of the mixed solution to 5.5-6.5 by using ammonia water, so as to optimize the synthesis conditions of the rare earth acetylacetone complex, ensure that the rare earth ions react fully with the acetylacetone molecules, and generate a high-purity rare earth acetylacetone complex. If the pH is not adjusted or adjusted improperly, the complex structure may be incomplete, the thermal stability and chemical stability may be reduced, and the performance in the subsequent material preparation process may be affected. For example, when the pH value of the mixed solution is lower than 5.5 or higher than 6.5, the synthesis reaction of the rare earth acetylacetone complex may be insufficient or unable to be synthesized or side reactions may occur, affecting the purity and quality of the product.
[0038] According to some preferred embodiments, the hexahydrate of the rare earth chloride is RECl3·6H2O, wherein RE is selected from one or more of La (lanthanum), Sm (samarium), Gd (gadolinium), Tb (terbium), Dy (dysprosium) or Yb (ytterbium); specifically, the hexahydrate of the rare earth chloride includes but is not limited to lanthanum chloride hexahydrate LaCl3·6H2O, samarium chloride hexahydrate SmCl3·6H2O, gadolinium chloride hexahydrate GdCl3·6H2O, terbium chloride hexahydrate TbCl3·6H2O, dysprosium chloride hexahydrate DyCl3·6H2 O or hexahydrate ytterbium chloride YbCl3·6H2O one or more; the hexahydrate of the rare earth nitrate is RE(NO3)3·6H2O, wherein RE is selected from one or more of La, Sm, Gd, Tb, Dy or Yb; specifically, the hexahydrate of the rare earth nitrate includes but is not limited to hexahydrate lanthanum nitrate La(NO3)3·6H2O, hexahydrate samarium nitrate Sm(NO3)3·6H2O, hexahydrate gadolinium nitrate Gd(NO3)3·6H2O, hexahydrate terbium nitrate Tb(NO3)3·6H2O, hexahydrate dysprosium nitrate D The present invention does not specifically limit the source of the rare earth chloride hexahydrate or the rare earth nitrate hexahydrate, and can use products that can be directly purchased or prepared by existing methods; the molar ratio of the rare earth chloride hexahydrate to acetylacetone is 1: (3-4) (for example, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8 or 1:4), and the molar ratio of the rare earth nitrate hexahydrate to acetylacetone is 1: (3-4) (for example, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8 or 1:4). The ethanol solution is an ethanol aqueous solution, and the volume percentage (volume fraction) of ethanol in the ethanol aqueous solution is 90-98% (for example, 90%, 92%, 94%, 96% or 98%); and / or the ammonia water is an ammonia water with a mass fraction of 20-30% (for example, 20%, 22%, 24%, 26%, 28% or 30%), that is, the mass fraction of ammonia in the ammonia water is 20-30%.
[0039] When preparing the rare earth acetylacetone complex in the present invention, it is preferred that the molar ratio of the hexahydrate of the rare earth chloride or the hexahydrate of the rare earth nitrate to acetylacetone is 1:(3-4), which is conducive to ensuring that the reaction is fully carried out and optimizing the product quality, and can ensure that the rare earth ions and the acetylacetone molecules react fully to generate a high-purity rare earth acetylacetone complex, avoid side reactions or residual uncoordinated rare earth ions, and help ensure that the structure of the formed complex is relatively complete, and the thermal stability and chemical stability are higher, which is conducive to maintaining the performance in the subsequent material preparation process.
[0040] According to some preferred embodiments, in step (3): the molar ratio of the rare earth acetylacetone complex to polyzirconoxane is 1:(1.5-3) (for example, 1:1.5, 1:2, 1:2.5 or 1:3), and the zirconium-rare earth ceramic precursor solution contains a sum of the mass fractions of the rare earth acetylacetone complex and polyzirconoxane of 40% to 60% (for example, 40%, 45%, 50%, 55% or 60%).
[0041] According to some preferred embodiments, in step (3): the molar ratio of the rare earth acetylacetone complex to the polyhafnium oxide is 1:(1.5-3) (for example, 1:1.5, 1:2, 1:2.5 or 1:3), and the hafnium-rare earth ceramic precursor solution contains a sum of the mass fractions of the rare earth acetylacetone complex and the polyhafnium oxide of 40% to 60% (for example, 40%, 45%, 50%, 55% or 60%).
[0042] When preparing the zirconium (hafnium)-rare earth ceramic precursor solution in the present invention, it is preferred that the molar ratio of the rare earth acetylacetone complex to polyzirconoxane (polyhafnium oxide) is 1: (1.5-3). The present invention uses a relatively low cracking temperature and does not require polyzirconoxane (or polyhafnium oxide) to completely complete the carbon thermal reduction reaction. The present invention finds that while an appropriately excessive amount of polyzirconoxane (or polyhafnium oxide) continues to crack to form zirconium carbide (or hafnium carbide), it also cracks to form zirconium oxide (or hafnium oxide); the present invention uses zirconium oxide (or hafnium oxide) as a zirconium source (or hafnium source), a rare earth acetylacetone complex as a rare earth source, and an oxygen-containing functional group in the precursor as an oxygen source to react to form a rare earth zirconate (or rare earth hafnium oxide) with better ablation resistance, thereby improving the ablation resistance and lowering the cracking temperature, reducing the carbon thermal reduction reaction and the erosion of the carbon fiber by oxygen in the precursor, which is beneficial to ensuring the mechanical properties of the fiber; the present invention finds that controlling the The molar ratio of the rare earth acetylacetone complex to polyzirconoxane (or polyhafnium oxide) is in the range of 1: (1.5-3), which is beneficial to ensure that the reaction is fully carried out and the product quality is optimized, and side reactions are avoided. It can not only ensure the uniformity and density of the material, but also effectively regulate the cracking temperature and oxygen consumption, which is beneficial to improving the ablation resistance and mechanical properties of the ceramic-based composite material. If the molar ratio is lower than 1: 1.5, the amount of polyzirconoxane (or polyhafnium oxide) is insufficient, and it cannot completely react with the rare earth acetylacetone complex to generate sufficient rare earth zirconate (or rare earth hafnium oxide), which will affect the ablation resistance. If the molar ratio is higher than 1: 3, the amount of the rare earth acetylacetone complex is insufficient, which may cause the direct precipitation of rare earth oxides instead of forming rare earth zirconate (or rare earth hafnium oxide), or the product is mainly zirconium oxide (or hafnium oxide), which will reduce the uniformity and density of the ceramic matrix and also affect the ablation resistance of the ceramic-based composite material.
[0043] According to some preferred embodiments, in the precursor impregnation pyrolysis process in step (4), the pyrolysis temperature is 1300-1500°C (e.g., 1300°C, 1350°C, 1400°C, 1450°C or 1500°C), and the pyrolysis time is 1.5-3h (e.g., 1.5, 2, 2.5, 3 or 3.5h); In the present invention, preferably, the pyrolysis temperature is 1300-1500°C, and the pyrolysis time is 1.5-3 .5h, within this temperature range, the long insulation time can ensure that the polyzirconium oxide (or polyhafnium oxide) is cracked to form zirconium carbide (or hafnium carbide), and at the same time, it fully reacts with the rare earth acetylacetone complex at high temperature to form rare earth zirconate (or rare earth hafnium salt); and / or the obtained carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or carbon fiber reinforced carbide ceramic-rare earth hafnium salt ceramic matrix composite material has a density of 2.2 to 2.5 g / cm 3 In the present invention, the precursor impregnation pyrolysis process (PIP process) is a well-known technology in the art. Those skilled in the art can use the PIP process to use a zirconium (hafnium)-rare earth ceramic precursor solution as an impregnation solution to perform multiple impregnation-curing-pyrolysis processes to densify the porous carbon fiber preform until the obtained carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material has a density of 2.2 to 2.5 g / cm 3 That is, the present invention does not specifically limit the number of times the PIP process is performed, and multiple impregnation-curing-cracking processes are performed until the density of the obtained carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material is 2.2-2.5 g / cm 3 That's it.
[0044] According to some preferred embodiments, in step (5): the molybdenum chloride is molybdenum tetrachloride (MoCl4); the silicon chloride is silicon tetrachloride (SiCl4); during chemical vapor infiltration, hydrogen (H2) and argon (Ar) are used as carrier gases; in step (5), MoSi2 is introduced into the carbon fiber reinforced carbide ceramic-rare earth zirconate (or rare earth hafniumate) ceramic matrix composite material by the CVI method to further improve the ablation resistance of the ceramic matrix composite material; during the CVI process, MoCl4 and SiCl4 are used as Mo sources and Si sources, and H2 and Ar are used as carrier gases; the pressure during chemical vapor infiltration is 50 to 200 mbar (for example, 50, 100, 150 or 200 mbar), and the temperature (working temperature) is 900 to 1000 °C. 1200°C (for example, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C); and / or during chemical vapor infiltration, the flow rate of the molybdenum chloride is 10-50sccm (for example, 10, 20, 30, 40 or 50sccm), the flow rate of the silicon chloride is 50-200sccm (for example, 50, 100, 150 or 200sccm), the flow rate of the hydrogen is 80-300sccm (for example, 80, 160, 240 or 300sccm), the flow rate of the argon is 100-400sccm (for example, 100, 200, 300 or 400sccm); in the present invention, the flow unit "sccm" means standard milliliters per minute. In the present invention, a carbon fiber reinforced carbide ceramic-rare earth zirconate (or rare earth hafnium salt) ceramic matrix composite material with a surface rich in MoSi2 is obtained after the CVI process, that is, the ceramic matrix composite material resistant to high temperature ablation described in the present invention is obtained; in the present invention, the introduced MoSi2 not only has excellent antioxidant and ablation resistance, but also can be used as a sintering aid to promote the sintering of zirconium carbide (or hafnium carbide) at high temperature, thereby further improving the ablation resistance of the ceramic matrix composite material; the present invention does not make a specific limitation on the time for chemical vapor infiltration, so that the density of the ceramic matrix composite material resistant to high temperature ablation is 2.7-3.0 g / cm 3 That's it.
[0045] In the present invention, when MoSi2 is introduced by the CVI method, it is preferred that the flow rate of the molybdenum chloride is 10-50sccm, the flow rate of the silicon chloride is 50-200sccm, the flow rate of the hydrogen is 80-300sccm, and the flow rate of the argon is 100-400sccm. The present invention can further fill MoSi2 in the ceramic-based composite material by controlling the appropriate flow rate of each component, thereby improving the density of the ceramic-based composite material, optimizing the antioxidant effect and extending the service life of the material, and significantly enhancing the thermal stability and load capacity of the ceramic-based composite material under high temperature environments; in addition, the use of chemical vapor infiltration can also increase the MoSi2 content in the surface layer of the ceramic-based composite material, promote the sintering of ZrC (or HfC) under high-temperature service environment, and improve the density of the oxide film, thereby improving the anti-ablation performance of the ceramic-based composite material; the present invention finds that if the flow rate of the molybdenum source or the silicon source is too low or too high, it will cause the product to deviate from the element stoichiometric ratio, the product is not a MoSi2 phase, and it is difficult to achieve the desired performance target.
[0046] According to some preferred embodiments, in step (5): chemical vapor infiltration is performed until the density of the obtained high temperature ablation resistant ceramic matrix composite material is 2.7 to 3.0 g / cm 3 (e.g. 2.7, 2.75, 2.8, 2.85, 2.9, 2.95 or 3.0 g / cm 3 ); The obtained high temperature ablation resistant ceramic matrix composite material is a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material with a surface rich in molybdenum disilicide or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material with a surface rich in molybdenum disilicide.
[0047] The second aspect of the present invention provides a high temperature ablation resistant ceramic matrix composite material prepared by the preparation method described in the first aspect of the present invention. The ceramic matrix composite material prepared by the present invention has excellent high temperature oxidation ablation resistance above 2000°C and excellent high temperature mechanical properties.
[0048] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments, and those skilled in the art may make various corresponding changes and deformations according to the present invention without departing from the spirit and essence of the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention.
[0049] Example 1
[0050] ①Preparation of porous carbon fiber preform: Provide a carbon fiber braid as a skeleton with a density of 0.5g / cm 3The carbon fiber braid is a carbon fiber needle-punched braid obtained by a needle-punched braiding method; a pyrolytic carbon interface layer is deposited on the carbon fibers of the carbon fiber braid by a chemical vapor deposition method (CVD method) to obtain a carbon fiber with a density of 0.91 g / cm 3 porous carbon fiber preform.
[0051] ② Preparation of rare earth acetylacetone complex: GdCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%) at a molar ratio of 1:3.5 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of GdCl3·6H2O and acetylacetone; then, ammonia water (25% ammonia water by mass) is used to adjust the pH value of the mixed solution to 6 and the mixture is kept at 60°C for 1.5 hours, filtered to obtain a crude product of a rare earth (Gd) acetylacetone complex, and then washed with an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%) The crystals are then dried at 70°C to obtain a rare earth (Gd) acetylacetone complex.
[0052] ③ Preparation of zirconium-rare earth ceramic precursor solution: Stir and mix the rare earth (Gd) acetylacetone complex and polyzirconoxane in a molar ratio of 1:2 in xylene at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a zirconium-rare earth ceramic precursor solution (Zr-Gd ceramic precursor solution), wherein the total mass amount of the rare earth (Gd) acetylacetone complex and polyzirconoxane is such that the total mass fraction of the rare earth (Gd) acetylacetone complex and polyzirconoxane in the zirconium-rare earth ceramic precursor solution is 50%.
[0053] ④PIP process densification: The zirconium-rare earth ceramic precursor solution obtained in step ③ was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced zirconium carbide ceramic-gadolinium zirconate ceramic matrix composite material was 2.3 g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1450°C, and the cracking insulation time at 1450°C is 2.5h.
[0054] ⑤ Further densification by CVI process: MoSi2 was introduced into the carbon fiber reinforced zirconium carbide ceramic-gadolinium zirconate ceramic matrix composite material obtained in step ④ by using MoCl4 and SiCl4 as raw materials, H2 and Ar as carrier gases through the CVI method; wherein, the gas pressure during the CVI process was 100 mbar, the working temperature was 1000 ° C, the CVI time was 50 hours, the MoCl4 flow rate was 30 sccm, the SiCl4 flow rate was 100 sccm, the H2 flow rate was 250 sccm, and the Ar flow rate was 350 sccm, and the density of the ceramic matrix composite material resistant to high temperature ablation was finally obtained. 2.83 g / cm 3 .
[0055] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 0.87×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 227MPa in an air environment of 1600°C.
[0056] Example 2
[0057] ①Preparation of porous carbon fiber preform: Provide a carbon fiber braid as a skeleton with a density of 0.55g / cm 3 The carbon fiber braid is a carbon fiber stitched braid obtained by stitching braiding method; a boron nitride interface layer is deposited on the carbon fibers of the carbon fiber braid by chemical vapor deposition (CVD method) to obtain a density of 0.84 g / cm 3 porous carbon fiber preform.
[0058] ② Preparation of rare earth acetylacetone complex: SmCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 90%) at a molar ratio of 1:3 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of SmCl3·6H2O and acetylacetone; then, ammonia water (20% ammonia water by mass) is used to adjust the pH value of the mixed solution to 5.5 and the mixture is kept warm at 60°C for 1.5 hours, filtered to obtain a crude product of a rare earth (Sm) acetylacetone complex, and then washed with an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 90%) The crystals are washed and then dried at 60°C to obtain a rare earth (Sm) acetylacetone complex.
[0059] ③ Preparation of hafnium-rare earth ceramic precursor solution: Stir and mix the rare earth (Sm) acetylacetone complex and polyhafnium oxide in a molar ratio of 1:1.5 in xylene at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a hafnium-rare earth ceramic precursor solution (Hf-Sm ceramic precursor solution), wherein the total mass amount of the rare earth (Sm) acetylacetone complex and the polyhafnium oxide is such that the total mass fraction of the rare earth (Sm) acetylacetone complex and the polyhafnium oxide in the hafnium-rare earth ceramic precursor solution is 40%.
[0060] ④PIP process densification: The hafnium-rare earth ceramic precursor solution obtained in step ③ was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced hafnium carbide ceramic-samarium hafnate ceramic matrix composite material was 2.20 g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1300°C, and the cracking insulation time at 1300°C is 3h.
[0061] ⑤ Further densification by CVI process: MoCl4 and SiCl4 are used as raw materials, H2 and Ar are used as carrier gases, and MoSi2 is introduced into the carbon fiber reinforced hafnium carbide ceramic-samarium hafnate ceramic matrix composite material obtained in step ④ by CVI method; wherein, the gas pressure in the CVI process is 50 mbar, the working temperature is 900 ° C, the CVI time is 50 hours, the MoCl4 flow rate is 10 sccm, the SiCl4 flow rate is 50 sccm, the H2 flow rate is 80 sccm, and the Ar flow rate is 100 sccm, and the density of the ceramic matrix composite material resistant to high temperature ablation is finally obtained. The density is 2.70 g / cm 3 .
[0062] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 0.98×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 202MPa in an air environment of 1600°C.
[0063] Example 3
[0064] ①Preparation of porous carbon fiber preform: Provide a carbon fiber braid as a skeleton with a density of 0.50g / cm 3 The carbon fiber braid is a carbon fiber puncture braid obtained by a puncture braiding method; a silicon carbide interface layer is deposited on the carbon fibers of the carbon fiber braid by a chemical vapor deposition method (CVD method) to obtain a density of 1.04 g / cm 3 porous carbon fiber preform.
[0065] ② Preparation of rare earth acetylacetone complex: DyCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 98%) at a molar ratio of 1:4 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of DyCl3·6H2O and acetylacetone; then, ammonia water (30% ammonia water by mass) is used to adjust the pH value of the mixed solution to 6.5 and the mixture is kept warm at 60°C for 1.5 hours, filtered to obtain a crude product of a rare earth (Dy) acetylacetone complex, and then washed with an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 98%) The crystals are then dried at 80°C to obtain a rare earth (Dy) acetylacetone complex.
[0066] ③ Preparation of zirconium-rare earth ceramic precursor solution: Stir and mix the rare earth (Dy) acetylacetone complex and polyzirconoxane in a molar ratio of 1:3 in xylene at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a zirconium-rare earth ceramic precursor solution (Zr-Dy ceramic precursor solution), wherein the total mass amount of the rare earth (Dy) acetylacetone complex and polyzirconoxane is such that the total mass fraction of the rare earth (Dy) acetylacetone complex and polyzirconoxane in the zirconium-rare earth ceramic precursor solution is 60%.
[0067] ④PIP process densification: The zirconium-rare earth ceramic precursor solution obtained in step ③ was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced zirconium carbide ceramic-dysprosium zirconate ceramic matrix composite material was 2.35 g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1500°C, and the cracking insulation time at 1500°C is 1.5h.
[0068] ⑤ Further densification by CVI process: MoSi2 was introduced into the carbon fiber reinforced zirconium carbide ceramic-dysprosium zirconate ceramic matrix composite material obtained in step ④ by using MoCl4 and SiCl4 as raw materials, H2 and Ar as carrier gases through the CVI method; wherein, the gas pressure during the CVI process was 100 mbar, the working temperature was 1000 ° C, the CVI time was 50 hours, the MoCl4 flow rate was 30 sccm, the SiCl4 flow rate was 100 sccm, the H2 flow rate was 250 sccm, and the Ar flow rate was 350 sccm, and the density of the ceramic matrix composite material resistant to high temperature ablation was finally obtained. 2.85 g / cm 3 .
[0069] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 0.84×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 248MPa in an air environment of 1600°C.
[0070] Example 4
[0071] ①Preparation of porous carbon fiber preform: Provide a carbon fiber braid as a skeleton with a density of 0.55g / cm 3 The carbon fiber braid is a carbon fiber needle-punched braid obtained by needle-punching. A pyrolytic carbon interface layer is deposited on the carbon fibers of the carbon fiber braid by chemical vapor deposition (CVD) to obtain a carbon fiber with a density of 1.17 g / cm 3 porous carbon fiber preform.
[0072] ② Preparation of rare earth acetylacetone complex: Tb(NO3)3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 92%) at a molar ratio of 1:3.2 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of Tb(NO3)3·6H2O and acetylacetone; then, ammonia water (22% ammonia water by mass) is used to adjust the pH value of the mixed solution to 5.7 and the mixture is kept warm at 60°C for 1.5 hours, filtered to obtain a crude product of the rare earth (Tb) acetylacetone complex, and then the crystals are washed with an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 92%), and then dried at 65°C to obtain a rare earth (Tb) acetylacetone complex.
[0073] ③ Preparation of hafnium-rare earth ceramic precursor solution: Stir and mix the rare earth (Tb) acetylacetone complex and polyhafnium oxide in a molar ratio of 1:2.5 in xylene at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a hafnium-rare earth ceramic precursor solution (Hf-Tb ceramic precursor solution), wherein the total mass amount of the rare earth (Tb) acetylacetone complex and the polyhafnium oxide is such that the total mass fraction of the rare earth (Tb) acetylacetone complex and the polyhafnium oxide in the hafnium-rare earth ceramic precursor solution is 55%.
[0074] ④PIP process densification: The hafnium-rare earth ceramic precursor solution obtained in step ③ was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced hafnium carbide ceramic-terbium hafnate ceramic matrix composite material was 2.29 g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1400°C, and the cracking insulation time at 1400°C is 3h.
[0075] ⑤ Further densification by CVI process: MoCl4 and SiCl4 are used as raw materials, H2 and Ar are used as carrier gases, and MoSi2 is introduced into the carbon fiber reinforced hafnium carbide ceramic-terbium hafnate ceramic matrix composite material obtained in step ④ by CVI method; wherein, the gas pressure in the CVI process is 100 mbar, the working temperature is 1000 ° C, the CVI time is 50 hours, the MoCl4 flow rate is 30 sccm, the SiCl4 flow rate is 100 sccm, the H2 flow rate is 250 sccm, and the Ar flow rate is 350 sccm, and the density of the ceramic matrix composite material resistant to high temperature ablation is finally obtained. 3 .
[0076] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 0.94×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 199 MPa in an air environment of 1600°C.
[0077] Example 5
[0078] ①Preparation of porous carbon fiber preform: Provide a carbon fiber braid as a skeleton with a density of 0.51g / cm 3 The carbon fiber braid is a carbon fiber needle-punched braid obtained by a needle-punched braiding method; a pyrolytic carbon interface layer is deposited on the carbon fibers of the carbon fiber braid by a chemical vapor deposition method (CVD method) to obtain a density of 0.82 g / cm 3 porous carbon fiber preform.
[0079] ② Preparation of rare earth acetylacetone complex: LaCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 94%) at a molar ratio of 1:3.8 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of LaCl3·6H2O and acetylacetone; then, ammonia water (28% ammonia water by mass) is used to adjust the pH value of the mixed solution to 6.3 and the mixture is kept warm at 60°C for 1.5 hours, filtered to obtain a crude product of a rare earth (La) acetylacetone complex, and then the crystals are washed with an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 94%), and then dried at 75°C to obtain a rare earth (La) acetylacetone complex.
[0080] ③ Preparation of zirconium-rare earth ceramic precursor solution: Stir and mix the rare earth (La) acetylacetone complex and polyzirconoxane in a molar ratio of 1:2.8 in xylene at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a zirconium-rare earth ceramic precursor solution (Zr-La ceramic precursor solution), wherein the total mass amount of the rare earth (La) acetylacetone complex and polyzirconoxane is such that the total mass fraction of the rare earth (La) acetylacetone complex and polyzirconoxane in the zirconium-rare earth ceramic precursor solution is 50%.
[0081] ④PIP process densification: The zirconium-rare earth ceramic precursor solution obtained in step ③ was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced zirconium carbide ceramic-lanthanum zirconate ceramic matrix composite material was 2.45g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1350°C, and the cracking insulation time at 1350°C is 2h.
[0082] ⑤ Further densification by CVI process: MoCl4 and SiCl4 are used as raw materials, H2 and Ar are used as carrier gases, and MoSi2 is introduced into the carbon fiber reinforced zirconium carbide ceramic-lanthanum hafnium oxide ceramic matrix composite material obtained in step ④ by CVI method; wherein, the gas pressure in the CVI process is 100 mbar, the working temperature is 1000 ° C, the CVI time is 50 hours, the MoCl4 flow rate is 30 sccm, the SiCl4 flow rate is 100 sccm, the H2 flow rate is 250 sccm, and the Ar flow rate is 350 sccm, and the density of the ceramic matrix composite material resistant to high temperature ablation is finally obtained. 2.92 g / cm 3 .
[0083] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 0.78×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 256 MPa in an air environment of 1600°C.
[0084] Example 6
[0085] Embodiment 6 is substantially the same as Embodiment 1, except that:
[0086] ③ Preparation of zirconium-rare earth ceramic precursor solution: Stir and mix the rare earth (Gd) acetylacetone complex and polyzirconoxane in a molar ratio of 1:1.2 in xylene at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a zirconium-rare earth ceramic precursor solution (Zr-Gd ceramic precursor solution), wherein the total mass amount of the rare earth (Gd) acetylacetone complex and polyzirconoxane is such that the total mass fraction of the rare earth (Gd) acetylacetone complex and polyzirconoxane in the zirconium-rare earth ceramic precursor solution is 50%.
[0087] When the subsequent step ④ of this embodiment is carried out, the same PIP process parameters and PIP times as those in step ④ of Example 1 are adopted. When the subsequent step ⑤ of this embodiment is carried out, the same CVI process parameters and CVI time as those in step ⑤ of Example 1 are adopted. The density of the ceramic matrix composite material finally prepared in this embodiment is 2.99 g / cm 3 .
[0088] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 1.22×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 173 MPa in an air environment of 1600°C.
[0089] Example 7
[0090] Example 7 is substantially the same as Example 1, except that:
[0091] ③ Preparation of zirconium-rare earth ceramic precursor solution: Stir and mix the rare earth (Gd) acetylacetone complex and polyzirconoxane in a molar ratio of 1:3.5 in xylene at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a zirconium-rare earth ceramic precursor solution (Zr-Gd ceramic precursor solution), wherein the total mass amount of the rare earth (Gd) acetylacetone complex and polyzirconoxane is such that the total mass fraction of the rare earth (Gd) acetylacetone complex and polyzirconoxane in the zirconium-rare earth ceramic precursor solution is 50%.
[0092] When the subsequent step ④ of this embodiment is carried out, the same PIP process parameters and PIP times as those in step ④ of Example 1 are adopted. When the subsequent step ⑤ of this embodiment is carried out, the same CVI process parameters and CVI time as those in step ⑤ of Example 1 are adopted. The density of the ceramic matrix composite material finally prepared in this embodiment is 2.72 g / cm 3 .
[0093] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 1.46×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 154 MPa in an air environment of 1600°C.
[0094] Example 8
[0095] Example 8 is substantially the same as Example 1, except that:
[0096] ② Preparation of rare earth acetylacetone complex: GdCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%) at a molar ratio of 1:2 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of GdCl3·6H2O and acetylacetone; then, ammonia water (25% by mass) is used to adjust the pH value of the mixed solution to 6 and the mixture is kept warm at 60°C for 1.5 hours, filtered to obtain a crude product of a rare earth (Gd) acetylacetone complex, and then the crystals are washed with an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%), and then dried at 70°C to obtain a rare earth (Gd) acetylacetone complex.
[0097] When the subsequent step ④ of this embodiment is carried out, the same PIP process parameters and PIP times as those in step ④ of embodiment 1 are adopted. When the subsequent step ⑤ of this embodiment is carried out, the same CVI process parameters and CVI time as those in step ⑤ of embodiment 1 are adopted. The density of the ceramic matrix composite material finally prepared in this embodiment is 2.63 g / cm 3 .
[0098] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 1.76×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 129 MPa in an air environment of 1600°C.
[0099] Example 9
[0100] Example 9 is substantially the same as Example 1, except that:
[0101] ② Preparation of rare earth acetylacetone complex: GdCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%) at a molar ratio of 1:5 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of GdCl3·6H2O and acetylacetone; then, ammonia water (25% ammonia water by mass) is used to adjust the pH value of the mixed solution to 6 and the mixture is kept warm at 60°C for 1.5 hours, filtered to obtain a crude product of a rare earth (Gd) acetylacetone complex, and then the crystals are washed with an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%), and then dried at 70°C to obtain a rare earth (Gd) acetylacetone complex.
[0102] When the subsequent step ④ of this embodiment is carried out, the same PIP process parameters and PIP times as those in step ④ of embodiment 1 are adopted. When the subsequent step ⑤ of this embodiment is carried out, the same CVI process parameters and CVI time as those in step ⑤ of embodiment 1 are adopted. The density of the ceramic matrix composite material finally prepared in this embodiment is 2.77 g / cm 3 .
[0103] Performance test: The high temperature ablation resistant ceramic matrix composite material prepared in this embodiment was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the high temperature ablation resistant ceramic matrix composite material was 2000°C, the test time was 600s, and the linear ablation rate of the high temperature ablation resistant ceramic matrix composite material was 1.65×10 -3 mm / s; it is measured that the high temperature ablation resistant ceramic matrix composite material prepared in this embodiment has a bending strength of 146MPa in an air environment of 1600°C.
[0104] Comparative Example 1
[0105] ①Same as step ① in Example 1.
[0106] ② Preparation of zirconium ceramic precursor solution: Stir polyzirconoxane and xylene at room temperature 25°C until uniformly mixed (stirring speed is 600 rpm, stirring time is 60 min) to obtain a zirconium ceramic precursor solution (Zr ceramic precursor solution), the mass amount of polyzirconoxane is such that the mass fraction of polyzirconoxane in the zirconium ceramic precursor solution is 50%.
[0107] ③PIP process densification: The zirconium ceramic precursor solution obtained in step ② was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced zirconium carbide ceramic matrix composite material was 2.47 g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1700°C, and the cracking insulation time at 1700°C is 2.5h.
[0108] ④ Further densification by CVI process: MoSi2 was introduced into the carbon fiber reinforced zirconium carbide ceramic matrix composite material obtained in step ③ by using MoCl4 and SiCl4 as raw materials, H2 and Ar as carrier gases through the CVI method; wherein, the gas pressure during the CVI process was 100 mbar, the working temperature was 1000 °C, the CVI time was 50 hours, the MoCl4 flow rate was 30 sccm, the SiCl4 flow rate was 100 sccm, the H2 flow rate was 250 sccm, and the Ar flow rate was 350 sccm, and the density of the ceramic matrix composite material finally obtained was 2.70 g / cm 3 .
[0109] Performance test: The ceramic matrix composite material finally prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material finally prepared was 1.57×10 -3 mm / s; it was measured that the ceramic-based composite material finally prepared in this comparative example had a flexural strength of 103 MPa in an air environment at 1600°C.
[0110] Comparative Example 2
[0111] ①Same as step ① of Example 1.
[0112] ②Same as step ② of Example 1.
[0113] ③ Preparation of rare earth ceramic precursor solution: The rare earth (Gd) acetylacetone complex and xylene are stirred and mixed evenly at room temperature 25°C (stirring speed is 600 rpm, stirring time is 60 min) to obtain a rare earth ceramic precursor solution (Gd ceramic precursor solution), wherein the mass dosage of the rare earth (Gd) acetylacetone complex is such that the mass fraction of the rare earth (Gd) acetylacetone complex in the rare earth ceramic precursor solution is 50%.
[0114] ④PIP process densification: The rare earth ceramic precursor solution obtained in step ③ was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced gadolinium oxide-based composite material was 2.27 g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1450°C, and the cracking insulation time at 1450°C is 2.5h.
[0115] ⑤ Further densification by CVI process: MoSi2 was introduced into the carbon fiber reinforced gadolinium oxide-based ceramic matrix composite material obtained in step ④ by using MoCl4 and SiCl4 as raw materials, H2 and Ar as carrier gases through the CVI method; wherein, the gas pressure during the CVI process was 100 mbar, the working temperature was 1000 ° C, the CVI time was 50 hours, the MoCl4 flow rate was 30 sccm, the SiCl4 flow rate was 100 sccm, the H2 flow rate was 250 sccm, and the Ar flow rate was 350 sccm, and the density of the ceramic matrix composite material finally obtained was 2.81 g / cm 3 .
[0116] Performance test: The ceramic matrix composite material prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material was 2.88×10 -3 mm / s; it was measured that the ceramic-based composite material prepared in this comparative example had a flexural strength of 117 MPa in an air environment at 1600°C.
[0117] Comparative Example 3
[0118] ①Same as step ① of Example 1.
[0119] ② Preparation of hafnium ceramic precursor solution: Stirring polyhafnium oxide and xylene at room temperature 25°C until uniformly mixed (stirring speed is 600 rpm, stirring time is 60 min) to obtain a hafnium ceramic precursor solution (Hf ceramic precursor solution), the mass amount of polyhafnium oxide is such that the mass fraction of polyhafnium oxide in the hafnium ceramic precursor solution is 50%.
[0120] ③PIP process densification: The hafnium ceramic precursor solution obtained in step ② was used as the impregnation solution, and the porous carbon fiber preform obtained in step ① was densified by 10 PIP processes. The density of the obtained carbon fiber reinforced hafnium carbide ceramic matrix composite material was 2.68 g / cm 3 ; Wherein, each PIP process includes impregnation, curing and cracking in sequence, the impregnation is vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes in sequence, the pressure of the vacuum impregnation is 200Pa, and the pressure of the pressurized impregnation is 1.5MPa; the curing is carried out in an argon atmosphere, the curing temperature is 260°C, and the curing time at 260°C is 1.5h; the cracking is carried out in an argon atmosphere, the cracking temperature is 1700°C, and the cracking insulation time at 1700°C is 2.5h.
[0121] ④ Further densification by CVI process: MoSi2 was introduced into the carbon fiber reinforced hafnium carbide ceramic matrix composite material obtained in step ③ by using MoCl4 and SiCl4 as raw materials, H2 and Ar as carrier gases through the CVI method; wherein, the gas pressure during the CVI process was 100 mbar, the working temperature was 1000 °C, the CVI time was 50 hours, the MoCl4 flow rate was 30 sccm, the SiCl4 flow rate was 100 sccm, the H2 flow rate was 250 sccm, and the Ar flow rate was 350 sccm, and the density of the ceramic matrix composite material finally obtained was 2.89 g / cm 3 .
[0122] Performance test: The ceramic matrix composite material finally prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material finally prepared was 1.48×10 -3 mm / s; it was measured that the ceramic-based composite material finally prepared in this comparative example had a flexural strength of 105 MPa in an air environment at 1600°C.
[0123] Comparative Example 4
[0124] Comparative Example 4 is substantially the same as Example 1, except that:
[0125] In step ④, the PIP process is performed multiple times until a density of 2.52 g / cm is obtained. 3 After the carbon fiber reinforced zirconium carbide ceramic-gadolinium zirconate ceramic matrix composite material is prepared, the CVI process in the subsequent step ⑤ is not carried out to introduce MoSi2.
[0126] Performance test: The ceramic matrix composite material finally prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material finally prepared was 1.41×10 -3 mm / s; it was measured that the ceramic-based composite material finally prepared in this comparative example had a flexural strength of 172 MPa in an air environment at 1600°C.
[0127] Comparative Example 5
[0128] Comparative Example 5 is substantially the same as Comparative Example 2, except that:
[0129] In step ④, the density is 2.27 g / cm 3 After the carbon fiber reinforced gadolinium oxide-based composite material is prepared, the CVI process in the subsequent step ⑤ is not carried out to introduce MoSi2.
[0130] Performance test: The ceramic matrix composite material finally prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material finally prepared was 3.76×10 -3 mm / s; it was measured that the ceramic-based composite material finally prepared in this comparative example had a flexural strength of 98 MPa in an air environment at 1600°C.
[0131] Comparative Example 6
[0132] Comparative Example 6 is substantially the same as Example 1, except that:
[0133] ② Preparation of rare earth acetylacetone complex: GdCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%) at a molar ratio of 1:3.5 to obtain a mixed solution and keep it at 60°C for 1.5 hours, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of GdCl3·6H2O and acetylacetone; after filtration, almost no crude product of the rare earth (Gd) acetylacetone complex can be obtained.
[0134] In this comparative example, since ammonia water was not used to adjust the pH of the mixed solution to 5.5-6.5 during the preparation of the rare earth acetylacetone complex, almost no crude product of the rare earth (Gd) acetylacetone complex was obtained, and subsequent operations could not be performed.
[0135] Comparative Example 7
[0136] Comparative Example 7 is substantially the same as Example 1, except that:
[0137] ② Preparation of rare earth acetylacetone complex: GdCl3·6H2O and acetylacetone are uniformly mixed in an ethanol aqueous solution (the volume fraction of ethanol in the ethanol aqueous solution is 95%) at a molar ratio of 1:3.5 to obtain a mixed solution, wherein the amount of the ethanol aqueous solution is 5 times the sum of the mass amounts of GdCl3·6H2O and acetylacetone; then, ammonia water (25% ammonia water by mass) is used to adjust the pH value of the mixed solution to 10 and keep it at 60°C for 1.5 hours. After filtration, it is also almost impossible to obtain a crude product of the rare earth (Gd) acetylacetone complex.
[0138] In this comparative example, since the pH of the mixed solution was adjusted too high by using ammonia water during the preparation of the rare earth acetylacetone complex, almost no crude product of the rare earth (Gd) acetylacetone complex was obtained, and subsequent operations could not be performed.
[0139] Comparative Example 8
[0140] With reference to Example 6 of CN 117602943 A, a ceramic-based composite material with a high sintering degree was prepared.
[0141] Performance test: The ceramic matrix composite material finally prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material finally prepared was 1.09×10 -3 mm / s; it was measured that the ceramic-based composite material finally prepared in this comparative example had a flexural strength of 164 MPa in an air environment at 1600°C.
[0142] Comparative Example 9
[0143] ①Same as step ① of Example 1.
[0144] ② Preparation of slurry: phenolic resin and hexamethylenetetramine were dissolved in anhydrous ethanol, and then GdCl3·6H2O was added and ball-milled for 24 hours to obtain a slurry; the mass ratio of phenolic resin to GdCl3·6H2O was 1:3, and the mass of hexamethylenetetramine was 0.1 times the mass of phenolic resin; the viscosity of the slurry was controlled to 76 mPa·s by the content of anhydrous ethanol.
[0145] ③ Vacuum pressure impregnation: Put the porous carbon fiber preform obtained in step ① and the slurry obtained in step ② into a vacuum tank at the same time, but without contacting each other, and evacuate for 20 minutes to make the vacuum degree -0.10MPa. Then immerse the porous carbon fiber preform in the slurry and maintain the pressure for 30 minutes, slowly increase the air pressure to 0.8MPa, maintain the pressure for 30 minutes and take it out.
[0146] ④ Curing and cracking: The material prepared in step ③ was dried in an oven at 80°C for 4 hours, cured in an oven at 140°C for 30 minutes, and then heat treated at 1500°C for 2 hours under argon protection to crack the phenolic resin.
[0147] ⑤ Reactive melt infiltration (RMI): Infiltrate zirconium powder into the material obtained in step ④ under vacuum conditions at 1700°C to react with C to generate ZrC in situ, thereby obtaining a C / ZrC-Gd ultra-high temperature ceramic matrix composite material.
[0148] ⑥ CVI process further densification: MoSi2 was introduced into the C / ZrC-Gd ultra-high temperature ceramic matrix composite material obtained in step ⑤ by CVI method using MoCl4 and SiCl4 as raw materials and H2 and Ar as carrier gases; wherein, the gas pressure during CVI process was 100 mbar, the working temperature was 1000 °C, the CVI time was 50 hours, the MoCl4 flow rate was 30 sccm, the SiCl4 flow rate was 100 sccm, the H2 flow rate was 250 sccm, and the Ar flow rate was 350 sccm, and the density of the ceramic matrix composite material finally obtained was 2.98 g / cm 3 .
[0149] Performance test: The ceramic matrix composite material finally prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material resistant to high temperature ablation was 1.44×10 -3 mm / s; it was measured that the flexural strength of the high-temperature ablation-resistant ceramic-based composite material finally prepared in this comparative example was 111 MPa in an air environment of 1600°C.
[0150] Comparative Example 10
[0151] ①Same as step ① of Example 1.
[0152] ②Same as step ② of Example 1.
[0153] ③ is the same as step ③ of Example 1.
[0154] ④ is the same as step ④ of Example 1.
[0155] ⑤ Dispersing molybdenum disilicide powder in isopropanol to obtain a molybdenum disilicide dispersion, wherein the concentration of molybdenum disilicide in the molybdenum disilicide dispersion is 35 g / L; placing the zirconium carbide ceramic-gadolinium zirconate ceramic-based composite material sample obtained in step ④ flat in a glass sand core filtration device, and then pouring the molybdenum disilicide dispersion into a vacuum filtration flat-bottomed funnel for filtration, the vacuum pump is evacuated to a pressure of -0.1 MPa, the air volume is 8 L / min, the power is 180 W, the frequency is 50 Hz, and the voltage is 22 0V; put the filtered sample into an electric hot air drying oven and dry it at 60℃ for 2h; put the dried sample into a 0.75mol / L glucose aqueous solution and perform homogeneous hydrothermal treatment at 180℃ for 8h, then take out the sample, put the taken sample into an electric hot air drying oven and dry it at 100℃ for 3h; put the dried sample into a vacuum furnace and heat treat it at 1500℃ for 1.5h under argon protection to obtain a density of 2.68g / cm 3 Ceramic matrix composites.
[0156] Performance test: The ceramic matrix composite material finally prepared in this comparative example was subjected to oxyacetylene ablation test according to GJB 323B-2018 standard. The surface temperature of the ceramic matrix composite material was 2000°C and the test time was 600s. The linear ablation rate of the ceramic matrix composite material was measured to be 1.32×10 -3 mm / s; it was measured that the ceramic-based composite material finally prepared in this comparative example had a flexural strength of 195 MPa in an air environment at 1600°C.
[0157] By comparing the examples with the comparative examples, it can be clearly seen that the high temperature ablation resistant ceramic matrix composite material provided by the present invention has excellent performance in high temperature ablation resistance and high temperature mechanical properties. Table 1 below shows the key parameters and performance test results of the ceramic matrix composite material prepared in each example and each comparative example.
[0158] Table 1
[0159]
[0160] The symbol “ / ” in Table 1 indicates that the parameter does not exist.
[0161] In the embodiments of the present invention, a rare earth acetylacetone complex is combined with a carbide precursor (such as polyzirconium oxide or polyhafnium oxide) to form composite precursors such as Zr-Gd, Hf-Sm, Zr-Dy, Hf-Tb, and Zr-La. These precursors can generate rare earth zirconates or rare earth hafnium oxides during the cracking process, which significantly improves the high-temperature ablation resistance and high-temperature mechanical properties of the composite material. However, comparative examples 1, 2, and 3 of the present invention only use a single carbide precursor or rare earth acetylacetone complex, and no rare earth zirconate or rare earth hafnium oxide is formed, and the ablation resistance and high-temperature mechanical properties are poor. In addition, the embodiments of the present invention all introduce MoSi2 with high ablation resistance, oxidation resistance, and the ability to promote the sintering of carbides through the CVI process, further improving the compactness and ablation resistance of the composite material. However, comparative examples 4 and 5 of the present invention do not perform the CVI process, and MoSi2 is not introduced into the composite material, resulting in a significant decrease in ablation resistance. The linear ablation rate of the ceramic matrix composite material finally prepared in the preferred embodiment of the present invention is 1.00×10 -3 mm / s or less, and the flexural strength in an air environment of 1600°C is above 199MPa, showing excellent high-temperature ablation resistance and high-temperature mechanical properties. However, the ceramic-based composite materials finally prepared in each comparative example have a high linear ablation rate, and their high-temperature ablation resistance is obviously inferior to that of the ceramic-based composite materials prepared in the preferred embodiment of the present invention, and their flexural strength in an air environment of 1600°C is relatively low.
[0162] In summary, the present invention significantly improves the high-temperature ablation resistance and high-temperature mechanical properties of carbon fiber reinforced ceramic matrix composites by combining rare earth acetylacetone complexes with carbide precursors and introducing MoSi2 through the CVI process.
[0163] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high temperature ablation resistant ceramic matrix composite material, characterized in that: The method comprises the following steps: (1) preparing a porous carbon fiber preform; (2) preparing a rare earth acetylacetone complex using a hexahydrate of a rare earth chloride or a hexahydrate of a rare earth nitrate and acetylacetone; (3) mixing the rare earth acetylacetone complex and polyzirconium oxide or polyhafnium oxide uniformly with xylene to obtain a zirconium-rare earth ceramic precursor solution or a hafnium-rare earth ceramic precursor solution; (4) using a zirconium-rare earth ceramic precursor solution or a hafnium-rare earth ceramic precursor solution as an impregnation liquid, and performing a first densification on the porous carbon fiber preform through a precursor impregnation and cracking process to obtain a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material; (5) Using molybdenum chloride and silicon chloride as raw materials, a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material is subjected to a second densification by a chemical vapor infiltration method to obtain a ceramic matrix composite material resistant to high temperature ablation.
2. The preparation method according to claim 1, characterized in that: In step (1): The porous carbon fiber preform is obtained by depositing an interface layer on the fibers of the carbon fiber braid; Preferably, the density of the carbon fiber braid is 0.4-0.6 / cm 3 ; Preferably, the interface layer is one or more of a pyrolytic carbon interface layer, a silicon carbide interface layer or a boron nitride interface layer; Preferably, the density of the porous carbon fiber preform is 0.7-1.2 g / cm 3 .
3. The preparation method according to claim 1, characterized in that: In step (2), the rare earth acetylacetone complex is prepared by: The hexahydrate of rare earth chloride or hexahydrate of rare earth nitrate is mixed with acetylacetone evenly with an ethanol solution to obtain a mixed solution, and then the pH of the mixed solution is adjusted to 5.5-6.5 with ammonia water and kept warm at 50-70°C for 1-2 hours, and then filtered, washed, crystallized and dried to obtain a rare earth acetylacetone complex.
4. The preparation method according to claim 3, characterized in that: The hexahydrate of the rare earth chloride is RECl3·6H2O, wherein RE is selected from one or more of La, Sm, Gd, Tb, Dy or Yb; The hexahydrate of the rare earth nitrate is RE(NO3)3·6H2O, wherein RE is selected from one or more of La, Sm, Gd, Tb, Dy or Yb; The molar ratio of the hexahydrate of the rare earth chloride to acetylacetone is 1:(3-4), and the molar ratio of the hexahydrate of the rare earth nitrate to acetylacetone is 1:(3-4); The ethanol solution is an ethanol aqueous solution, and the volume percentage of ethanol in the ethanol aqueous solution is 90-98%; and / or The ammonia water has a mass fraction of 20 to 30%.
5. The preparation method according to claim 1, characterized in that: In step (3): The molar ratio of the rare earth acetylacetone complex to polyzirconia is 1:(1.5-3), and the zirconium-rare earth ceramic precursor solution contains 40%-60% of the sum of the mass fractions of the rare earth acetylacetone complex and polyzirconia.
6. The preparation method according to claim 1, characterized in that: In step (3): The molar ratio of the rare earth acetylacetone complex to the polyhafnium oxide is 1:(1.5-3), and the hafnium-rare earth ceramic precursor solution contains the sum of the mass fractions of the rare earth acetylacetone complex and the polyhafnium oxide of 40%-60%.
7. The preparation method according to claim 1, characterized in that: In the precursor impregnation and cracking process in step (4): The pyrolysis temperature is 1300-1500°C, and the pyrolysis time is 1.5-3h; and / or The obtained carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material or carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material has a density of 2.2-2.5 g / cm 3 .
8. The preparation method according to claim 1, characterized in that: In step (5): The molybdenum chloride is molybdenum tetrachloride; The silicon chloride is silicon tetrachloride; When chemical vapor infiltration is performed, hydrogen and argon are used as carrier gases; The pressure during chemical vapor infiltration is 50-200 mbar and the temperature is 900-1200° C.; and / or During chemical vapor infiltration, the flow rate of the molybdenum chloride is 10-50 sccm, the flow rate of the silicon chloride is 50-200 sccm, the flow rate of the hydrogen is 80-300 sccm, and the flow rate of the argon is 100-400 sccm.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (5): Chemical vapor infiltration is performed until the density of the obtained high temperature ablation resistant ceramic matrix composite material is 2.7 to 3.0 g / cm 3 ; The obtained high temperature ablation resistant ceramic matrix composite material is a carbon fiber reinforced carbide ceramic-rare earth zirconate ceramic matrix composite material with a surface rich in molybdenum disilicide or a carbon fiber reinforced carbide ceramic-rare earth hafniumate ceramic matrix composite material with a surface rich in molybdenum disilicide.
10. A high temperature ablation resistant ceramic matrix composite material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of carbon fiber-reinforced ultra high-temperature ceramic-base composite material capable of being repeatedly ablated for use
CN103864451A
A c / c‑sic‑mosi 2 Preparation method of ceramic matrix composite material
CN105237025B
Carbon-fiber-reinforced zirconium carbide composite material and preparation method therefor
CN105367106A
High-sintering-degree ceramic-based composite material and preparation method thereof
CN117602943A
Cited By
Polypropylene composite material based on rare earth element modification and preparation method and application thereof
CN120329652A
Polypropylene composite material based on rare earth element modification and preparation method and application thereof
CN120329652B
Preparation method of asphalt-based hard felt
CN120794672A
A method for preparing bitumen-based rigid felt
CN120794672B